2021
DOI: 10.1186/s40663-021-00311-1
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of oak deforestation and rainfed cultivation on soil redistribution processes across hillslopes using 137Cs techniques

Abstract: Background As one of the main components of land-use change, deforestation is considered the greatest threat to global environmental diversity with possible irreversible environmental consequences. Specifically, one example could be the impacts of land-use changes from oak forests into agricultural ecosystems, which may have detrimental impacts on soil mobilization across hillslopes. However, to date, scarce studies are assessing these impacts at different slope positions and soil depths, shedd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 70 publications
0
5
0
Order By: Relevance
“…In addition to soil textural effects, other geomorphic and biochemical processes (e.g. topography, physical and chemical weathering, biological activity, water flow patterns) may affect crop response at a specific location in the landscape (Hallema et al 2016, Ayoubi et al 2021. The variation (spatial and temporal) in such physical and chemical processes is often considered during crop placement at the field scale (Thelemann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to soil textural effects, other geomorphic and biochemical processes (e.g. topography, physical and chemical weathering, biological activity, water flow patterns) may affect crop response at a specific location in the landscape (Hallema et al 2016, Ayoubi et al 2021. The variation (spatial and temporal) in such physical and chemical processes is often considered during crop placement at the field scale (Thelemann et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…Yield was not significantly affected by drought, as all soil types had a high available water capacity. Other researchers also highlighted that differences in soil texture and topography influenced yield variability at the field spatial scale (Manoli et al, 2015;Hallema et al, 2016;Fang, Su, 2019;Neupane, Guo, 2019;Ayoubi et al, 2021), especially during dry years, when water reserves and water available to the plants were strongly influenced by a local soil texture. For example, Fang and Su (2019) reported that in dryland farming, sandy loam soils showed a more significant decrease in crop productivity and an increase in N leaching losses compared to loamy soils.…”
Section: Discussionmentioning
confidence: 99%
“…While SLs have generally increased the fluvial connectivity by transporting large amounts of sediment and runoff from hillslope to the valley bottom after generating within the lanes and/or collecting from surroundings (Boardman, 2013). Measuring disconnectivity in the process of sediment flux (Ondráčková and Máčka, 2019; Poeppl et al, 2020), hydrological and geochemical transfers (Fuller and Death, 2018; Lemm et al, 2021), multidimensional coupling on hillslopes (Ayoubi et al, 2021) is an emerging field of research in the anthropo-geomorphological investigation. However, most of these studies have overlooked the role of TIs on the alteration of such geomorphic processes, although roads and railways are ubiquitous features in all landscapes.…”
Section: Effects On Major Geomorphological Processes On Hillslope And...mentioning
confidence: 99%